2004
DOI: 10.1111/j.1365-3040.2004.01253.x
|View full text |Cite
|
Sign up to set email alerts
|

OsAGAP, an ARF‐GAP from rice, regulates root development mediated by auxin in Arabidopsis

Abstract: Arf (ADP-ribosylation factor) proteins, which mediate vesicular transport, have little or no intrinsic GTPase activity. They rely on the action of GTPase-activating proteins (GAPs) and guanine nucleotide exchange factors (GEFs) for their function. In the present study the OsAGAP gene in rice, which encoded a protein with predicted structure similar to ArfGAP, was identified. The purified OsAGAP-GST fusion protein was able to stimulate the GTPase activity of rice Arf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 62 publications
1
30
0
Order By: Relevance
“…To monitor in vitro GTP hydrolysis by His-LeoA and HisLeoADG, 1 mg purified protein was added to the Enzchek Phosphate assay kit (Molecular Probes), which provides a sensitive GTPase assay system used previously to study the activity of a related family of GTPases (Zhuang et al, 2005). GTP hydrolysis was assayed every 15 s for 5 min by measuring the change in absorbance at 360 nm (Fig.…”
Section: Leoa Is a Gtpasementioning
confidence: 99%
“…To monitor in vitro GTP hydrolysis by His-LeoA and HisLeoADG, 1 mg purified protein was added to the Enzchek Phosphate assay kit (Molecular Probes), which provides a sensitive GTPase assay system used previously to study the activity of a related family of GTPases (Zhuang et al, 2005). GTP hydrolysis was assayed every 15 s for 5 min by measuring the change in absorbance at 360 nm (Fig.…”
Section: Leoa Is a Gtpasementioning
confidence: 99%
“…Supporting this is that numerous proteins with GAP and sec7 domains have been identified by sequence analysis of the entire Arabidopsis (Arabidopsis thaliana) genome (Vernoud et al, 2003;Memon, 2004). However, of these large numbers of proteins, only a few have been studied in detail (Steinmann et al, 1999;Jensen et al, 2000;Koizumi et al, 2005;Zhuang et al, 2005;Sieburth et al, 2006). Arabidopsis ZAC, a protein that bears homology to the GAP domain of Arf GAPs, can activate the GTPase activity of Arf1 in vitro.…”
mentioning
confidence: 99%
“…In addition, several mutants have been identified that have mutations in the genes encoding Arf GAPs. These mutants displayed various phenotypes, such as a defect in auxin efflux and vein patterning, indicating that Arf GAPs play a role in these functions (Koizumi et al, 2005;Zhuang et al, 2005;Sieburth et al, 2006).…”
mentioning
confidence: 99%
“…The physiological roles of some of these AGD isoforms have been demonstrated through their mutant phenotypes: agd3/van3/sfc, nev/ agd5, and rpa/agd10 displayed defects in vein formation, floral organ shedding, and the growth of root hairs and pollen tubes, respectively (Koizumi et al, 2005;Sieburth et al, 2006;Song et al, 2006;Min et al, 2007;Yoo et al, 2008;Hwang and Robinson, 2009). In rice (Oryza sativa), OsAGAP is involved in vein patterning and root development (Zhuang et al, 2005). However, the functional mechanisms of these AGDs that underlie the observed developmental processes are largely unknown.…”
mentioning
confidence: 99%